Accessing awareness and developing knowledge - McGrath, Patrick (Brooks/Cole, 1999)
This is a workbook designed for multicultural counseling courses in psychology, counselor education, social work, and the human service/mental health professions. The workbook can be used with or without the main text, COUNSELING AND DEVELOPMENT IN A MULTICULTURAL SOCIETY, 3RD, by John Axelson. The course is often a required component of a master's level program in counselor education